Les traces de Denis Papin dans la poussière de l’histoire - Maguire, Conor (Comptes Rendus. Mécanique)
Denis Papin’s greatest achievement was undoubtedly recognizing the potential of steam to perform mechanical work. In this, he stands in a long line of great minds throughout history who have strived to harness the power of steam to operate mechanical devices. This lineage includes Hero of Alexandria (born in 10 BC) who invented the aeolipile steam turbine around two thousand years ago, and even before him, Archimedes (born in 287 BC) who invented one of the earliest steam devices. However, these devices apparently had no practical application at the time.In this article, we explore Papin’s efforts to create practical devices and the subsequent imprints he left in the literature, which can be considered a cultural artifact containing part of the “DNA” of human society. We employ bibliometric techniques to analyze the published literature (books, manuscripts, patents, etc.) from the 17th to the 21st century to quantitatively trace Papin’s impressive influence on science and technology.